2022
DOI: 10.1007/s10008-022-05251-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of metal oxide incorporated Al-Zn-Sn sacrificial anodes processed by stir casting and heat treatment

Abstract: Aluminum sacrificial anodes are currently the first choice for cathodic protection in numerous applications. The galvanic performance of aluminum-based sacrificial anodes is considerably enhanced by addition of certain alloying elements called activators. Recent researches proved that incorporation of specific metal oxides like MnO2, CeO2, RuO2, and IrO2 into the aluminum matrix could enhance the galvanic efficiency of aluminum anodes; however, the mechanism by which metal oxides improve galvanic properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Several studies have shown that Pb and Bi have synergistic effects, improving the active dissolution and current efficiency of aluminum alloys. Moreover, studies have demonstrated that the total content of both elements should not exceed 5% [11]. However, no in-depth study on Al-Ga-In alloy sacrificial anodes has been conducted yet.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that Pb and Bi have synergistic effects, improving the active dissolution and current efficiency of aluminum alloys. Moreover, studies have demonstrated that the total content of both elements should not exceed 5% [11]. However, no in-depth study on Al-Ga-In alloy sacrificial anodes has been conducted yet.…”
Section: Introductionmentioning
confidence: 99%